2019
DOI: 10.1111/imj.14322
|View full text |Cite
|
Sign up to set email alerts
|

Elevated D‐dimer levels predict adverse outcomes in hospitalised elderly patients with chronic heart failure

Abstract: Background Elevated D‐dimer levels have been associated with poor outcomes in patients with cardiovascular disease. Aim To study this association in elderly patients with chronic heart failure (CHF). Methods We analysed 1355 elderly patients who were admitted with CHF. All patients had D‐dimer levels measured within the first 24 h following admission. A multivariate logistic regression model was used to assess the variables associated with chronic kidney disease. We used Cox regression analysis to assess the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…19,20 Heart failure is not usually associated with DIC; however, elevated D-dimer levels were observed in patients with heart failure in the present study and in previous studies. 21 The mechanism of D-dimer elevation in patients with heart failure was reported to involve hemostatic abnormality and to predict a poor outcome. In this study, there were many trauma patients without organ failure who only had simple bone fracture.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Heart failure is not usually associated with DIC; however, elevated D-dimer levels were observed in patients with heart failure in the present study and in previous studies. 21 The mechanism of D-dimer elevation in patients with heart failure was reported to involve hemostatic abnormality and to predict a poor outcome. In this study, there were many trauma patients without organ failure who only had simple bone fracture.…”
Section: Discussionmentioning
confidence: 99%
“…What was different to us is that D‐dimer was found to be associated with cardiovascular mortality in hospitalized patients with HFrEF in another study 31 . A recent research also revealed that higher D‐dimer levels were associated with an increased risk of all‐cause death irrespective of the subtypes of HF including HFrEF and HFpEF 32 . The difference among these results may be that our study was conducted in the AMI population accompanied by HFpEF, HFrEF, or non‐HF during the index admission, but the other studies were only conducted in the pure HF population or coronary heart disease population.…”
Section: Discussionmentioning
confidence: 74%
“…31 A recent research also revealed that higher D-dimer levels were associated with an increased risk of all-cause death irrespective of the subtypes of HF including HFrEF and HFpEF. 32 The difference among these results may be that our study was conducted in the AMI population accompanied by HFpEF, HFrEF, or non-HF during the index admission, but the other studies were only conducted in the pure HF population or coronary heart disease population. HFpEF and HFrEF are two distinct HF phenotypes with different etiologic factors and pathophysiologic mechanism.…”
Section: Comparison With Existing Literaturementioning
confidence: 85%
“…Heart failure, a condition present in all COMMANDER-HF patients is, in itself, an hypercoagulable state that may both increase D-dimer and thrombotic events 8,15 . Along with HF re-hospitalization, the all-cause and cardiovascular death risk were higher even for plasma D-dimer concentrations within the "normal" range (<250 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Along with HF re-hospitalization, the all-cause and cardiovascular death risk were higher even for plasma D-dimer concentrations within the "normal" range (<250 ng/mL). Heart failure rehospitalization was by far the most common outcome event in COMMANDER-HF and hospitalized patients may present slightly elevated plasma D-dimer concentrations and have a high risk of dying, which might explain why relatively low plasma D-dimer concentrations were associated with fatal events 15,16 . In a post-hoc analysis of the ARISTOTLE (Apixaban versus Warfarin in Patients with Atrial Fibrillation) trial, higher plasma D-dimer concentrations were independently associated with increased risk of stroke/systemic embolic events, all-cause and cardiovascular death, and major bleeds 17 .…”
Section: Discussionmentioning
confidence: 99%